OPTIMALISASI IMPLEMENTASI KURIKULUM MERDEKA BELAJAR BERBASIS PEMBELAJARAN AKTIF DAN TEKNOLOGI UNTUK MENINGKATKAN KOMPETENSI GENERASI SOCIETY 5.0 - Aslan Aslan; Nashran Azizan (Adiba Aisha Amira, 2025)
This study aims to examine the optimal strategy for implementing the Merdeka Belajar (Freedom of Learning) Curriculum based on active learning and technology in order to improve the competence of the younger generation in the Society 5.0 era. The Merdeka Curriculum is a form of educational transformation that offers flexibility, project-based learning, and character building and technological literacy. Through a literature review method, this study collects and analyses various national and international literature sources relevant to the implementation of the Merdeka Curriculum, active learning, technology integration, and the competency needs of the 21st century generation. The results of the study indicate that the optimisation strategy involves strengthening teacher competencies, utilising digital learning technology, developing project-based and differentiated learning models, and multi-stakeholder collaboration. However, its implementation in the field still faces various challenges such as infrastructure limitations, low digital literacy, and readiness gaps between regions. Therefore, systemic and collaborative efforts are needed to realise an effective Merdeka Curriculum, so that it can produce Pancasila-based learner profiles who are ready to face the dynamics of Society 5.0.